Intellectual property rights in agroforestry: Issues and concerns for the farmers - Dev, Inder; Dhyani, S.K.; Handa, A.K.; Tiwari, Rupali (Indian Journal of Agroforestry, 2020)
Agroforestry can provide a variety of functions or benefits to farmers and communities and the most easily identifiable are the tree products, services provided by trees as well as biodiversity and microclimate regulation. The farmer today has to face consequences of declining land holdings, degradations of soil and water resources, inadequate credit support and negligible opportunities of non-farm employment. Intellectual property rights are an invaluable tool of increasingly knowledge-based economies. Presently advantage in the economic sector is led by information and competitiveness in research and development. Any innovation made by the farmers’ /researchers/ communities could be protected under IPR act for their benefits. The various categories of IPR can play a crucial role under Agroforestry particularly in the area of geographical indicators, trade mark, traditional knowledge and the Farmer’s Rights etc. Farmers have been playing a great role to conserve and enrich varieties and the knowledge they hold on the total genetic variability of the country. Hence importance of these rights from the conservation point of view becomes more compelling with the grant of Plant Breeder’s Rights to the breeders and Farmer’s Rights to the farmers. Despite the positive aspects of the Plant Variety Protection and Farmers Right Act 2001, farmer in India, many a times loses his rights as an innovator. In this paper various issues related to IPR in agroforestry as well issues and concerns of farmers are discussed.